PENERAPAN METODE KETERAMPILAN PROSES SAINS MELALUI MODEL BOUNDED INQUIRY LABORATORY SISWA SMAN 1 ULAKAN TAPAKIS - Har, Erman; Purnama Sari, Reski; Indra, Ristapawa; Ahmad, Aprizal; Roza, Welya (Cerdas Proklamator, 2022)
The purpose of this study was to determine whether the use of the Listening Team type of cooperative learning model could improve student learning outcomes. This research was conducted in two cycles, each cycle consisting of three meetings. The subjects of this study were the fourth grade students of SD Negeri 16 Surau Gadang, Nanggalo Padang District, totaling 32 people.The research instruments used in this study were student learning process observation sheets, teacher learning process observation sheets and student learning outcomes. 68.7 percent and the average score at the end of the second cycle is 80.47 with a learning completeness percentage of 87.5 percent. Analysis of the student process observation sheet obtained the average percentage in the first cycle was 66.9 percent while in the second cycle the average percentage obtained was 83 percent. This means that the implementation of science learning through the Listening Team type cooperative learning model is going well. The results obtained can be concluded that learning science through cooperative learning model type Listening Team can improve the process and learning outcomes of fourth grade students of SD Negeri 16 Surau Gadang, Nanggalo Padang District.